Legislative control of psychotropic substances in private clinics: a study on the existing laws in Malaysia / Arnie Fadzilah, Umikalsom Ibrahim and Maria Nazura Md. Nasir. - Fadzilah, Arnie; Ibrahim, Umikalsom; Md. Nasir, Maria Nazura (Faculty of Law, 2009)
In Malaysia, the abuse of psychotropic substances in private clinics is of concern unless strict controls are imposed because it can create more drug problems and it will show a bad image of the country. Abuse of psychotropic substances occurs when the medical practitioners are found involved in unlawful practices such as supply not for medical treatment, failure to maintain records and not having a proper storage. Even though legislations and enforcement programs exist, the problem persists. Enforcement of the laws by the relevant authorities is still inadequate to curb the problems. This research project is set out to examine the existing laws, which relates to the psychotropic substances in order to determine whether it is adequate to control abuse of psychotropic substances in the private clinics. It highlights the reasons of inadequacy of the relevant authorities in controlling the psychotropic substances in private clinics. This research uses the qualitative research methodology. Information is gathered from Law Journals, Law Reports, articles, books and semi-structured interviews. Through the research, it can be found that weaknesses of the enforcement are the main factor contributing to the problem of abuse of psychotropic substances in private clinics in Malaysia. The existing legislation is able to control the substances; however, improvement should be done such as in the definition of terms and the punishment imposed. Thus, there is a need to improve the laws, the enforcement approaches and the practices of medical practitioner in handling the psychotropic substances.